Answers

2015-01-21T09:18:29+08:00
Let  x+7y=23 be our equation 1
let 
12x+11y=23 be our equation 2

x+7y=23
12x+11y=23

Multiply ‐12 to our equation 1 and we get

‐12x‐84y=‐276 ‐‐‐‐‐‐> let ‐12x‐84y=‐276 be our equation 3.

now let's add equations 2 and 3

                      12x+11y=23
                 +
                     ‐12x‐84y=‐276
we get
‐73y = ‐253

Divide both sides by ‐73 and we get the value of y
y=253/73

Let us substitute the value of y in equation 2.
12x + 11(253/73) = 23
12x +2583/73 = 23
12x = (‐2583/73) +23
12x = ‐1104/73

divide both sides by 12 and we get the value of x
x= ‐92/73

Therefore, y = 253/73 and x = 
‐92/73
0